2015
DOI: 10.1186/s12863-015-0260-6
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic diversity influences the severity of Pseudomonas aeruginosa pneumonia in the Collaborative Cross mice

Abstract: BackgroundPseudomonas aeruginosa is one of the top three causes of opportunistic infections in humans. Patients with a compromised immune system, due to immunosuppressive therapies or underlying diseases such as cancer, AIDS or the hereditary disease cystic fibrosis, are at risk of developing P. aeruginosa infection. However, clinical evidence indicates extremely variable outcomes of P. aeruginosa infections in individuals at risk, suggesting that host multi-complex genetic traits may influence the severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…More recently, incipient CC lines were used to identify variants in Trim55 associated with vascular cuffing after infection with a mouse adapted SARS-CoV strain (Gralinski et al, 2015) and QTLs for survival to Klebsiella pneumoniae infection (Vered et al, 2014). Importantly, CC mice have been used to create improved models of EBOV (Ebola virus) and WNV (West Nile virus) infection (Graham et al, 2016;Graham et al, 2015;Rasmussen et al, 2014) and mouse populations showing diverse susceptibility to M. tuberculosis and Pseudomonas aeruginosa (Lore et al, 2015;Smith et al, 2016). These models await genome-wide scans to unveil the genetic determinants of infection susceptibility and severity.…”
Section: Mouse Studiesmentioning
confidence: 99%
“…More recently, incipient CC lines were used to identify variants in Trim55 associated with vascular cuffing after infection with a mouse adapted SARS-CoV strain (Gralinski et al, 2015) and QTLs for survival to Klebsiella pneumoniae infection (Vered et al, 2014). Importantly, CC mice have been used to create improved models of EBOV (Ebola virus) and WNV (West Nile virus) infection (Graham et al, 2016;Graham et al, 2015;Rasmussen et al, 2014) and mouse populations showing diverse susceptibility to M. tuberculosis and Pseudomonas aeruginosa (Lore et al, 2015;Smith et al, 2016). These models await genome-wide scans to unveil the genetic determinants of infection susceptibility and severity.…”
Section: Mouse Studiesmentioning
confidence: 99%
“…How the host genetic background mediates disease outcome and pathogenesis of chronic lung infection by shaping the host response to P. aeruginosa remains to be established. Phenotype/genotype correlations are difficult to approach in humans, while phylogenetically different strains of mice have been successfully used to clarify aspects of different susceptibility to P. aeruginosa infection5678910. In mouse strains presenting deviant clinical phenotypes, a faster and higher cell-mediated innate immune response sets the conditions for resistance during early P. aeruginosa infection, as opposed to susceptible phenotype9.…”
mentioning
confidence: 99%
“…In a recent study, scientists used the CC mouse model to determine whether the host genetic background could impact the risk of morbidity and mortality to pneumonia caused by infection with P. aeruginosa. In this study, the CC strain reproduced the responses of disease severity commonly observed in humans during infection, suggesting that variations in morbidity and mortality are highly affected by host genetic factors [105]. Whereas no significant gender differences on disease phenotypes were observed, it is important to note the sample size was small.…”
Section: Strain Differences and Associated Mechanismsmentioning
confidence: 71%
“…The CC combines the genomes of eight genetically diverse founder strains, such as A/J, C57BL/6 J, 129S1/SvImJ, NOD/LtJ, NZO/HlLtJ, CAST/EiJ, PWK/PhJ, and WSB/ EiJ [85]. This genetic combination is a significant element for the study on human-host susceptibility to major diseases, including infections, such as pneumonia [105]. In a recent study, scientists used the CC mouse model to determine whether the host genetic background could impact the risk of morbidity and mortality to pneumonia caused by infection with P. aeruginosa.…”
Section: Strain Differences and Associated Mechanismsmentioning
confidence: 99%